Percepção ambiental sobre a geração e disposição de resíduos sólidos urbanos sob o ponto de vista de membros de uma comunidade religiosa - Neves, Stephanie Oliveira (Universidade Federal de São Carlos, 2023)
The rapid and uncontrolled growth of cities has caused changes and impacts on the environment. Among the environmental problems resulting from urbanization, inadequate solid waste management stands out, which is related to the increase in production and diversity of materials. Thus, the objective of this research was to analyze the environmental perception of a religious community located in the Vila Sônia neighborhood, in the western zone of São Paulo, regarding the disposal and generation of solid waste of domestic origin, through the application of a semi-structured questionnaire. The research was conducted from November 2022 to January 2023. With the data obtained, it was possible to verify that the population has an understanding of the impacts that urban solid waste causes to the environment and understands the relevance of waste segregation. However, despite this understanding, it was found that the population consumes a large amount of products/foods with plastic packaging, which reflects a lack of awareness about the subject, given the impact that these materials have on the environment. As for waste segregation, it was possible to observe engagement by a large part of the interviewees. For the interviewees who do not separate their waste, it was found that the majority justifies this by the lack of selective collection in the neighborhood. With this, it was possible to conclude that there is a need for public engagement from the public power to implement selective collection programs in neighborhoods, so that the entire population can be served and have their rights guaranteed. In addition to verifying the need to sensitize and raise environmental awareness among people, strengthening knowledge about solid waste, so that they have a comprehensive understanding between thinking and acting, and thus develop healthier habits for the environment.
Environmental perception on the generation and disposal of urban solid waste from the point of view of members of a religious community
Keywords: Lixo urbano; Impactos ambientais; Conscientização ambiental; Sensibilização ambiental; Urban trash; Environmental impacts; Environmental awareness; Environmental awareness-raising; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS